2017
DOI: 10.1051/0004-6361/201730410
|View full text |Cite
|
Sign up to set email alerts
|

The potassium abundance in the globular clusters NGC 104, NGC 6752 and NGC 6809

Abstract: We derived Potassium abundances in red-giant-branch stars in the Galactic globular clusters NGC 104 (144 stars), NGC 6752 (134 stars), and NGC 6809 (151 stars) using high-resolution spectra collected with FLAMES at the ESO -Very Large Telescope. In the samples we consider, we do not find significant intrinsic spreads in [K/Fe], which confirms the previous findings , but which is at variance with the cases of the massive clusters NGC 2419 and NGC 2808.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 54 publications
4
34
1
Order By: Relevance
“…For them, the average abundance ratios obtained by Carretta et al (2013) The sample-averaged K abundance obtained in the study of 144 RGB stars in 47 Tuc by Mucciarelli et al (2017), [K/Fe] 1D NLTE = −0.12 ±0.08, is somewhat lower than that determined in Paper I, [K/Fe] RGB = 0.05 ± 0.13. This difference may be a result of the different microturbulent velocties used in the two studies: the sample-averaged value in Mucciarelli et al (2017) is ξ t = 1.66 km/s while in our analysis we used 1.5 km/s. Our tests show that the difference of 0.16 km/s in ξ t would lead to an ∼ 0.13 dex decrease in the average [K/Fe] ratio determined in Paper I using RGB stars.…”
Section: Average Abundances and Intrinsic Abundance Spreads In 47 Tucmentioning
confidence: 66%
See 3 more Smart Citations
“…For them, the average abundance ratios obtained by Carretta et al (2013) The sample-averaged K abundance obtained in the study of 144 RGB stars in 47 Tuc by Mucciarelli et al (2017), [K/Fe] 1D NLTE = −0.12 ±0.08, is somewhat lower than that determined in Paper I, [K/Fe] RGB = 0.05 ± 0.13. This difference may be a result of the different microturbulent velocties used in the two studies: the sample-averaged value in Mucciarelli et al (2017) is ξ t = 1.66 km/s while in our analysis we used 1.5 km/s. Our tests show that the difference of 0.16 km/s in ξ t would lead to an ∼ 0.13 dex decrease in the average [K/Fe] ratio determined in Paper I using RGB stars.…”
Section: Average Abundances and Intrinsic Abundance Spreads In 47 Tucmentioning
confidence: 66%
“…These findings support our earlier results obtained in the analysis of Na, Mg, and K abundances in 32 RGB stars in Paper I, where we found no statistically significant relations in the abundance-abundance, abundance-distance, and abundanceabsolute radial velocity planes. On the other hand, a study of 144 RGB stars in 47 Tuc by Mucciarelli et al (2017) revealed statistically significant [K/Fe] − [Na/Fe] correlation and [K/Fe] − [O/Fe] anti-correlation (in the same study, such correlations were also detected in the globular cluster NGC 6752). In their analysis, Mucciarelli et al (2017) used Spearman's nonparametric rank-order correlation coefficients, r s , and computed the two-tailed probability, p, that in a given dataset r s could attain a value that is equal to or larger than its measured value.…”
Section: Relations Between the Abundances Of Light Elements And Evolumentioning
confidence: 79%
See 2 more Smart Citations
“…A targeted search for [K/Fe] in other globular clusters (NGC 6752, NGC 6121, NGC 1904, NGC 104, NGC 6397, NGC 7099, and ω Centauri) and field stars concluded that all K abundance ratios fell within the bounds of the Mg-normal population in NGC 2419 (Carretta et al 2013), and no correlations between Mg and K were observed. Recent work byČerniauskas et al (2017) searched for unusual abundance patterns in Mg and K in NGC 104 by deriving abundances using 2dF/HERMES spectra, and a more comprehensive study involving over 400 stars in NGC 104, NGC 6752, and NGC 6809 by Mucciarelli et al (2017) using FLAMES spectra (Černiauskas et al 2017 both found no correlations between Mg and K, and no significant intrinsic spreads in either Mg or K. NGC 2808 is the only cluster, other than NGC 2419, where an anticorrelation between Mg and K has been observed. All four of NGC 2808's known Mg-depleted stars show an anti-correlation with K (Mucciarelli et al 2015), although the amplitude of these abundance ratios is far weaker than those found in NGC 2419.…”
Section: Introductionmentioning
confidence: 99%